Consumption of spicy foods and total and cause specific mortality: population based cohort study. (4th August 2015) - Lv, Jun; Qi, Lu; Yu, Canqing; Yang, Ling; Guo, Yu; Chen, Yiping; Bian, Zheng; Sun, Dianjianyi; Du, Jianwei; Ge, Pengfei; Tang, Zhenzhu; Hou, Wei; et al.
Abstract : Objective To examine the associations between the regular consumption of spicy foods and total and cause specific mortality. Design Population based prospective cohort study. Setting China Kadoorie Biobank in which participants from 10 geographically diverse areas across China were enrolled between 2004 and 2008. Participants 199 293 men and 288 082 women aged 30 to 79 years at baseline after excluding participants with cancer, heart disease, and stroke at baseline. Main exposure measures Consumption frequency of spicy foods, self reported once at baseline. Main outcome measures Total and cause specific mortality. Results During 3 500 004 person years of follow-up between 2004 and 2013 (median 7.2 years), a total of 11 820 men and 8404 women died. Absolute mortality rates according to spicy food consumption categories were 6.1, 4.4, 4.3, and 5.8 deaths per 1000 person years for participants who ate spicy foods less than once a week, 1 or 2, 3 to 5, and 6 or 7 days a week, respectively. Spicy food consumption showed highly consistent inverse associations with total mortality among both men and women after adjustment for other known or potential risk factors. In the whole cohort, compared with those who ate spicy foods less than once a week, the adjusted hazard ratios for death were 0.90 (95% confidence interval 0.84 to 0.96), 0.86 (0.80 to 0.92), and 0.86 (0.82 to 0.90) for those who ate spicy food 1 or 2, 3 to 5, and 6 or 7 days a week, respectively. Compared with those who ate spicy foods less than once a week, those who consumed spicy foods 6 or 7 days a week showed a 14% relative risk reduction in total mortality. The inverse association between spicy food consumption and total mortality was stronger in those who did not consume alcohol than those who did (P=0.033 for interaction). Inverse associations were also observed for deaths due to cancer, ischemic heart diseases, and respiratory diseases. Conclusion In this large prospective study, the habitual consumption of spicy foods was inversely associated with total and certain cause specific mortality, independent of other risk factors of death.